The Monoclonal Antitoxin Antibodies (Actoxumab–Bezlotoxumab) Treatment Facilitates Normalization of the Gut Microbiota of Mice with Clostridium difficile Infection - Džunková, Mária; D'Auria, Giuseppe; Xu, Hua; Huang, Jun; Duan, Yinghua; Moya, Andrés; Kelly, Ciarán P.; Chen, Xinhua (Frontiers in Cellular and Infection Microbiology, 2016)
Antibiotics have significant and long-lasting impacts on the intestinal microbiota and consequently reduce colonization resistance against Clostridium difficile infection (CDI). Standard therapy using antibiotics is associated with a high rate of disease recurrence, highlighting the need for novel treatment strategies that target toxins, the major virulence factors, rather than the organism itself. Human monoclonal antibodies MK-3415A (actoxumab-bezlotoxumab) to C. difficile toxin A and toxin B, as an emerging non-antibiotic approach, significantly reduced the recurrence of CDI in animal models and human clinical trials. Although the main mechanism of protection is through direct neutralization of the toxins, the impact of MK-3415A on gut microbiota and its restoration has not been examined. Using a CDI murine model, we compared the bacterial diversity of the gut microbiome of mice under different treatments including MK-3415A, vancomycin or vancomycin combined with MK-3415A, sampled longitudinally. Here we showed that C. difficile infection resulted in the prevalence of Enterobacter species. 60% of mice in the vehicle group died after two days and their microbiome was almost exclusively formed by Enterobacter. MK-3415A treatment resulted in lower Enterobacter levels and restoration of Blautia, Akkermansia and Lactobacillus which were the core components of the original microbiota. Vancomycin treatment led to significantly lower survival rate than the combo treatment of MK-3415A and vancomycin. Vancomycin treatment decreased bacterial diversity with predominant Enterobacter and Akkermansia, while Staphylococcus expanded after vancomycin treatment was terminated. In contrast, mice treated by vancomycin combined with MK-3415A also experienced decreased bacterial diversity during vancomycin treatment. However, these animals were able to recover their initial Blautia and Lactobacillus proportions, even though episodes of Staphylococcus overgrowth were detected by the end of the experiments. In conclusion, MK-3415A (actoxumab-bezlotoxumab) treatment facilitates normalization of the gut microbiota in CDI mice. It remains to be examined whether or not the prevention of recurrent CDI by the antitoxin antibodies observed in clinical trials occurs through modulation of microbiota.